The island of dr. libris eaudiobook - Grabenstein, Chris (Listening Library, 2015)
New from the author of Escape from Mr. Lemoncello’s Library and coauthor of the I Funny series with James Patterson! Celebrate the power of imagination with this action-packed New York Times bestseller that shows that sometimes the real story starts after you close the book!    What if your favorite characters came to life? Billy’s spending the summer in a lakeside cabin that belongs to the mysterious Dr. Libris. But something strange is going on. Besides the security cameras everywhere, there’s Dr. Libris’s private bookcase. Whenever Billy opens the books inside, he can hear sounds coming from the island in the middle of the lake. The clash of swords. The twang of arrows. Sometimes he can even feel the ground shaking. It’s almost as if the stories he’s reading are coming to life! But that’s impossible . . . isn’t it?   “ A wonderful tale . . . . This book is like no other I’ve read. It’s a complete original .” —James Patterson "Kids will enjoy the cartoonish mayhem , especially given Grabenstein's breezy narrative voice and jaunty wit ....as in 'Lemoncello', there is a winning generosity and sweetness to the story's telling." —The New York Times "Chris Grabenstein gleefully plunders great works of literature for his cast of secondary characters . . . a madcap mash-up that 8-to-12 year olds will want to devour in big gulps ." — The Wall Street Journal " Effortlessly readable and a whole lot of fun ." — Booklist Reviews